Foundations of entrepreneurship and economic development - Harper, David A. (Foundations of the market economy series., 2003)
This well-written book is the first to deal with entrepreneurship in all its aspects. It considers the economic, psychological, political, legal and cultural dimensions of entrepreneurship from a market-process perspective.